2020
DOI: 10.1002/csc2.20055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating herbicide tolerance of industrial hemp (Cannabis sativa L.)

Abstract: Industrial hemp (Cannabis sativa L.) has a wide array of end uses which, when coupled with regulatory reductions in the United States, has spurred renewed interest in its production. Best management practices, including weed control, need to be evaluated. Since little is known about herbicide tolerance of hemp, studies were conducted to identify suitable options for grain or dual‐purpose (fiber and grain) production. Greenhouse experiments with pre‐emergence and postemergence herbicides were conducted to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…Amaducci et al (2015) advised against planting hemp in years following maize treated with atrazine. Metribuzin was found to reduce stand and plant height and to cause >70% biomass reduction in greenhouse applications (Flessner et al 2020). Fomesafen has been found to cause significant biomass reduction and highly variable injury (Flessner et al 2020;Maxwell 2016).…”
Section: Preemergence Herbicidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Amaducci et al (2015) advised against planting hemp in years following maize treated with atrazine. Metribuzin was found to reduce stand and plant height and to cause >70% biomass reduction in greenhouse applications (Flessner et al 2020). Fomesafen has been found to cause significant biomass reduction and highly variable injury (Flessner et al 2020;Maxwell 2016).…”
Section: Preemergence Herbicidesmentioning
confidence: 99%
“…Metribuzin was found to reduce stand and plant height and to cause >70% biomass reduction in greenhouse applications (Flessner et al 2020). Fomesafen has been found to cause significant biomass reduction and highly variable injury (Flessner et al 2020;Maxwell 2016). Flessner et al (2020) found that encapsulated acetochlor did not reduce stand or height in greenhouse trials, but they did not test nonencapsulated acetochlor.…”
Section: Preemergence Herbicidesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, weeds can still emerge through holes in plastic mulch and compete with the crop. U.S. producers typically rely on herbicides to control weeds, but there are currently no herbicides labeled for use in hemp in the United States (Flessner et al, 2020). Lack of control options makes understanding the effects of weeds on hemp yield and chemical composition a research priority (Ellison, 2021).…”
mentioning
confidence: 99%